2021
DOI: 10.1016/j.asmr.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Analysis Is Lacking in Abstracts Presented at Arthroscopy Association of North America and American Orthopaedic Society for Sports Medicine Annual Meetings From 2016 to 2019

Abstract: Purpose To evaluate the presence of sex-specific analysis (SSA) in abstracts accepted for podium presentation at the Arthroscopy Association of North America (AANA) and American Orthopaedic Society for Sports Medicine (AOSSM) annual meetings from 2016 to 2019. Methods Abstracts accepted for podium presentation at the AANA and AOSSM annual meetings from 2016 to 2019 were selected for review. Studies that included sex as a variable in a multifactorial statistical model we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…To improve our understanding of the impacts of sex and gender, there needs to be more consistent consideration and reporting of sex or gender-based differences in preclinical (sex-based) or clinical (sex and gender) research across health conditions than is currently being done. A review of podium presentations at the Arthroscopy Association of North America (AANA) and American Orthopaedic Society for Sports Medicine (AOSSM) meetings over a 4year period found that only 10% of studies included sexspecific analyses 13 . A review of 6 orthopaedic journals (2 general, 4 subspecialty) assessed articles published in 2016, including more than 700 studies and 24 million patients, and found that one-third of the articles analyzed data by sex and/ or gender 14 .…”
mentioning
confidence: 99%
“…To improve our understanding of the impacts of sex and gender, there needs to be more consistent consideration and reporting of sex or gender-based differences in preclinical (sex-based) or clinical (sex and gender) research across health conditions than is currently being done. A review of podium presentations at the Arthroscopy Association of North America (AANA) and American Orthopaedic Society for Sports Medicine (AOSSM) meetings over a 4year period found that only 10% of studies included sexspecific analyses 13 . A review of 6 orthopaedic journals (2 general, 4 subspecialty) assessed articles published in 2016, including more than 700 studies and 24 million patients, and found that one-third of the articles analyzed data by sex and/ or gender 14 .…”
mentioning
confidence: 99%